The immunochemical cross-reactivity between cytoplasmic and mitochondrial mammalian lysyl-tRNA synthetases - Sidorik, L.L.; Rybkinska, T.A.; Bakhiya, N.G.; Rodnin, N.V.; Filonenko, V.V.; Entelis, N.S.; Tarassov, I.A.; Martin, R.P.; Matsuka, G.Kh. (Биополимеры и клетка, 2000)
Animal and fungal cells (in contrast to prokaryotes) contain two distinct sets of related aminoacyl-tRNA synthetases (aaRSs) encoded by nuclear genes and functioning in cytosol and mitochondria. The structural differences between mitochondrial and cytoplasmic enzymes may reflect the functional adaptation to fulfil mitochondrial processes in addition to protein synthesis. Mitochondrial import of nuclearencoded tRNAs has been described in yeast, plants and protozoans but it has not been observed in mammalian cells. Ifs established that mitochondrial lysyl-tRNA synthetase (MSK) plays a prominent role in the transport of tRNA into yeast mitochondria for complementation o f mitochondrial tRNAs genes mutations. We tried to identify MSK homologues in mammalian cells with the help of monospecific antibodies against pre-MSK by ELISA and Western-blot analysis. We have identified cross-reactive proteins in mitochondrial and cytoplasmic fractions of mammalian cell lysates. These data, together with the results of cross-aminoacylation on mitochondrial and cytoplasmic tRNAs, suggest the presence of common antigenic determinants in the mitochondrial and cytoplasmic lysyl-tRNA synthetases from higher animals.